2011 IEEE Statistical Signal Processing Workshop (SSP) 2011
DOI: 10.1109/ssp.2011.5967771
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary techniques for the synthesis of 2-D FIR filters

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…if D fitness (ch current ,ch inspected ) ≥ f 1 continue else if D gene (ch current ,ch inspected ) ≥ g 1 continue else discard ch inspected ⎧ ⎨ ⎩ (19) ch current (ch inspected ) stands for chromosome current as Δ fitness (resp.Δ gene ) stands for distance in the fitness space and f ε (resp. g ε ) is a predefined threshold.…”
Section: Selection Scheme Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…if D fitness (ch current ,ch inspected ) ≥ f 1 continue else if D gene (ch current ,ch inspected ) ≥ g 1 continue else discard ch inspected ⎧ ⎨ ⎩ (19) ch current (ch inspected ) stands for chromosome current as Δ fitness (resp.Δ gene ) stands for distance in the fitness space and f ε (resp. g ε ) is a predefined threshold.…”
Section: Selection Scheme Refinementmentioning
confidence: 99%
“…Some evolutionary filter design methods have been implemented [2,8,13,16,17] for about 10 years with promising results. We have already investigated GA for designing one-dimensional (1D) and 2D FIR filters [18][19][20] by developing dedicated GAs for the synthesis of 1D and 2D FIR filters. We demonstrated that by adding some flexibility in classical GA versions, ripples can be significantly reduced compared to the traditional and genetic approaches [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several theorems have been proposed by Shanks et al (1972), Huang (1972, Strintzis (1977), De Carlo et al (1977, Jury (1978), Bose (1982). In addition, Lu and Lee (1985) developed a Lyapunov stability based approach for 2-D systems and Mastorakis et al (2003) described a design method with respect to constrained optimization for the design of the 2-D recursive digital filter.…”
Section: The Stability Of 2-d Digital Filtersmentioning
confidence: 99%
“…It combines filter design knowhow and expertise in the application of various GAs for different optimization problems. A preliminary version of the algorithm has already been presented in Boudjelaba [30,31]. This version has been improved by a better selection scheme and simplification of the parameter management.…”
Section: Advanced Pso and Filter Designmentioning
confidence: 99%